Looking into the Performance-Based Financing Black Box : Evidence from an Impact Evaluation in the Health Sector in Cameroon - de Walque, Damien; Robyn, Paul Jacob; Saidou, Hamadou; Sorgho, Gaston; Steenland, Maria (World Bank, Washington, DC, 2017)
Performance-based financing is a complex health system intervention aimed at improving coverage and quality of care. This paper presents the results of an impact evaluation in Cameroon that seeks to isolate the role of specific components of the performance-based financing approach on outcomes of interest, such as explicit financial incentives linked to results, additional resources available at the point of service delivery (not linked to performance), and enhanced supervision, coaching, and monitoring. Four evaluation groups were established to measure the effects of each component that was studied. In general, the results indicate that performance-based financing in Cameroon is an efficient mechanism to channel payments and funding to the provider level, leading to significant increases in utilization in the performance-based financing arm for several services (child and maternal vaccinations and use of modern family planning), but not for others, such as antenatal care visits and facility-based deliveries. However, for many of those outcomes, the differences between the performance-based financing group and the additional financing group are not significant. In terms of quality, performance-based financing was found to have a significant impact on the availability of essential inputs and equipment, qualified health workers, reduction in formal and informal user fees, and increased satisfaction among patients and providers. However, there was a clear effect of additional financing, irrespective of whether it was linked to incentives, in combination with reinforced supervision through performance-based financing. This result suggests that enhanced supervision and monitoring on their own are not sufficient to improve maternal and child health outcomes.